Non-invasive dual fluorescence in vivo imaging for detection of macrophage infiltration and matrix metalloproteinase (MMP) activity in inflammatory arthritic joints - Cho, Hongsik (Biomed Opt Express, 2016)
Detection and intervention at an early stage is a critical factor to impede arthritis progress. Here we present a non-invasive method to detect inflammatory changes in joints of arthritic mice. Inflammation was monitored by dual fluorescence optical imaging for near-infrared fluorescent (750F) matrix-metalloproteinase activatable agent and allophycocyanin-conjugated anti-mouse CD11b. Increased intensity of allophycocyanin (indication of macrophage accumulation) and 750F (indication of matrix-metalloproteinase activity) showed a biological relationship with the arthritis severity score and the histopathology score of arthritic joints. Our results demonstrate that this method can be used to detect early stages of arthritis with minimum intervention in small animal models.